2018
DOI: 10.3899/jrheum.170326
|View full text |Cite
|
Sign up to set email alerts
|

Growth During Tocilizumab Therapy for Polyarticular-course Juvenile Idiopathic Arthritis: 2-year Data from a Phase III Clinical Trial

Abstract: Among patients with pcJIA at Tanner stage ≤ 3 at baseline, 72% (74/103) had increased height SDS at the end of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…Exploratory analysis of growth showed that the distribution of height velocities was consistent with World Health Organization normative values ( Supplementary Fig. S5 , available at Rheumatology online) and in line with observations for pJIA and sJIA with i.v.-TCZ [ 34 , 35 ].…”
Section: Resultssupporting
confidence: 83%
“…Exploratory analysis of growth showed that the distribution of height velocities was consistent with World Health Organization normative values ( Supplementary Fig. S5 , available at Rheumatology online) and in line with observations for pJIA and sJIA with i.v.-TCZ [ 34 , 35 ].…”
Section: Resultssupporting
confidence: 83%
“…TCZ therapy allowed for the discontinuation of steroids in 47% of these patients (31 of 66 patients) by week 104. As reported elsewhere (28), this reduction in glucocorticoid exposure, together with the degree of disease control achieved, is considered clinically relevant based on improved growth profiles. On average, mild-to-moderate disability (29) at baseline improved with TCZ treatment over a 2-year period.…”
mentioning
confidence: 82%
“…In a small trial in 19 patients, 100% of patients met the criteria for a good response after 48 weeks of treatment with tocilizumab 95 . In a pivotal phase III trial and its subsequent long-term extension study in 188 patients, inhibition of IL-6 led to sustained and clinically meaningful improvements after 2 years, and skeletal growth was also improved by treatment with tocilizumab 96,97 . Another antibody to IL-6R, sarilumab, is in phase II trials for polyarticular JIA 98 and sJIA 99 .…”
Section: Il-6 Inhibition In Jia and Aosdmentioning
confidence: 99%